Bioactivity of essential oils extracted from Cupressus macrocarpa branchlets and Corymbia citriodora leaves grown in Egypt - Mohamed Z. M. Salem; Hosam O. Elansary; Hayssam M. Ali; Ahmed A. El-Settawy; Mohamed S. Elshikh; Eslam M. Abdel-Salam; Krystyna Skalicka-Woźniak (BMC, 2018)
Abstract Background Cupressus macrocarpa Hartw and Corymbia citriodora (Hook.) K.D. Hill & L.A.S. Johnson, widely grown in many subtropical areas, are used for commercial purposes, such as in perfumery, cosmetics, and room fresheners. Their potential as a source of antimicrobial compounds may be useful in different applications. Methods The chemical composition of essential oils (EOs) from C. macrocarpa branchlets and C. citriodora leaves was analyzed by using gas chromatography-mass spectrometry (GC/MS). Antibacterial and antifungal activities were assessed by the micro-dilution method to determine the minimum inhibitory concentrations (MICs), and minimum fungicidal concentrations (MFCs), and minimum bactericidal concentrations (MBCs). Further, the antioxidant capacity of the EOs was determined via 2,2'-diphenypicrylhydrazyl (DPPH) and β-carotene-linoleic acid assays. Results Terpinen-4-ol (23.7%), α-phellandrene (19.2%), α-citronellol (17.3%), and citronellal were the major constituents of EO from C. macrocarpa branchlets, and α-citronellal (56%), α-citronellol (14.7%), citronellol acetate (12.3%), isopulegol, and eucalyptol were the primary constituents of EO from C. citriodora leaves. Antibacterial activity with MIC values of EO from C. citriodora leaves was ranged from 0.06 mg/mL to 0.20 mg/mL, and MBC from 0.12 mg/mL against E. coli to 0.41 mg/mL. EO from C. macrocarpa branchlets showed less activity against bacterial strains. The MIC values against tested fungi of the EO from C. citriodora ranged from 0.11 to 0.52 mg/mL while for EO from C. macrocarpa from 0.29 to 3.21 mg/mL. The MIC and MFC values of EOs against P. funiculosum were lower than those obtained from Ketoconazole (KTZ) (0.20; 0.45; 0.29 and 0.53 mg/mL, respectively, vs 0.21 and 0.41 mg/mL. Antioxidant activity of the EO from C. citriodora was higher than that of the positive control but lower than that of the standard butylhydroxytoluene (BHT) (IC50 = 5.1 ± 0.1 μg/mL). Conclusion The results indicate that the EO from Egyptian trees such as C. citriodora leaves may possesses strong bactericidal and fungicidal activities and can be used as an agrochemical for controlling plant pathogens and in human disease management which will add crop additive value.